Algebra for Parents : A Book for Grown-Ups About Middle School Mathematics - Aharoni, Ron (Singapore, World Scientific Publishing Co. Pte. Ltd., 2021)
"The book goes through middle school mathematics and techniques and methods of its teaching. It is meant to aid parents who wish to be involved in the mathematical education of their children, as well as teachers who wish to learn principles of mathematics and of its teaching"-
Keywords: Algebra -- Study and teaching; Algebra -- Study and teaching (Middle school).